Steady-state pharmacokinetics and bioavailability of immediate-release and extended-release formulations of lamotrigine in elderly epilepsy patients: Use of stable isotope methodology - Polepally, Akshanth R. (J Clin Pharmacol, 2015)
A two-period, crossover bioavailability study was conducted to evaluate the relative and absolute bioavailability of immediate (IR) and extended-release (XR) lamotrigine formulations under steady-state conditions in elderly patients with epilepsy. On treatment days, each subject's morning dose (IR or XR lamotrigine) was replaced with an intravenous 50 mg dose of stable-labeled lamotrigine. Lamotrigine concentrations were measured at 13 time points between 0 and 96 hours. XR and IR lamotrigine formulations were similar with respect to steady-state area-under-the-concentration-time curve (AUC(0-24), (ss)), average concentration (Cavg(ss)) and trough concentration (Cτ(ss)). A 33% lower fluctuation in concentrations with XR was observed relative to IR lamotrigine. The time to peak concentration (Tmax(ss)) was delayed for XR lamotrigine (3.0 hours vs. 1.3 hours) with lower peak concentration (15% lower). The absolute bioavailability for IR and XR formulations were 73% and 92%, respectively. The formulations were bioequivalent with respect to AUC(0-24 h, ss), Cτ(ss), and Cavg(ss) indicating that it may be possible to switch directly from IR to XR lamotrigine without changes in the total daily dose.